Catur Guru Dalam Seni Pertunjukan Wayang Wong Millenial - Ruastiti Ni Made (Mudra Jurnal Seni Budaya, 2021)
This scientific work aims to discuss the concept and implementation of Catur Guru in the Millennial Wayang Wong Performing Arts. As a result of qualitative research, data collection was carried out through document study, observation, and in-depth interviews with dance teachers, artist representatives, and Balinese socio-cultural observers. All data collected were analyzed qualitatively using pedagogical theory and social action theory. The results showed that : First, Catur Guru is an educational concept that includes Guru Swadyaya (God Almighty), Guru Wisesa, Guru Pengajian, and Guru Rupaka. Second, the Wayang Wong Millennial performance art tells the story of Cupu Manik Astagina. Cupu Manik Astagina is a form of the implementation of Catur Guru, namely : 1) arousing awareness to always serve God as a self-help teacher, 2) the role and support of government officials as Guru Wisesa to support, care and mediate the educational process relate the Wayang Wong Bali, 3) the role of teachers in schools as Guru Pengajian, who guide their students to love the arts and culture of their nation and, 4) the role of parents as in educating their children. Wayang Wong Millennial also teaches Balinese children, who involved as Millennial Wayang Wong artist are expected to be creative, skilled at communicating, able to work together and collaborate, be able to think critically and be ready to compete in global competitions. In that case, teachers and parents of students need to assist their children in accessing online sites to support their physical growth and social and spiritual quotion.